HEAVY METALS POLLUTION FOR SOILS IN SOME OF ROADS AND SQUARES OFBAGHDAD CITY CENTER - S. K. Essa,; D. A. AL- jibury, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study aimed to assess of status pollution by heavy metals Cadmium, Lead, Zinc, and Nickel for soils in some of interior streets and squares of Baghdad city, evaluate the relation between heavy metals concentration in soil, and using some global pollution indexesfor calculating state of contamination of soils study area (Enrichment Factor (EF), Contamination Factor (CF), Pollution Load Index (PLI), Geoaccumulation index (Igeo). Study area was included the roads of Baghdad City Center. Four main interior roads were chosen in this study which is (Outer Karada, Al- Saadoon, Nidhal and Palestine). Results showed that heavy metals concentrations in soil samples took the following order Zn > Ni > Pb > Cd and all was higher than their concentration in comparison soils. The impact of traffic momentum, especially at public intersections on the concentrations of heavy metals in soils interior streets of Baghdad city, regardless of the traffic density. The results of calculation the values of pollution indexes (EF, CF, PLI and Igeo) that heavy metals concentrations were from human activities (anthropogenic source), which support an assumption of those soils affected by gasses emitted from vehicle exhausts and fly ash or other human activities.